The role of analysis of EVER2 haplotypes in actinic keratosis - Agnieszka Kalińska-Bienias; Grażyna Kostrzewa; Magdalena Malejczyk; Rafał Płoski; Sławomir Majewski (Termedia Publishing House, 2016)
Introduction . Polymorphisms of EVER genes are related to increased risk of actinic keratosis (AK), squamous skin cancers (SCC) and cervical cancer. Objective . The aim of this study was to analyze the haplotypes of the EVER 2 gene in 65 subjects with ≥ 5 actinic keratoses and in 274 controls. The correlations between EVER 2 haplotype and selected clinical parameters in patients with actinic keratosis were also evaluated. Material and methods . The analysis involved polymorphisms -917A>T (rs7208422), -988-4G>T (rs62079073) and -1107G>A (rs12452890), which obtained statistically significant results in previous published studies of patients with actinic keratosis and squamous skin cancers. The full blood samples of patients and controls were genotyped using real-time polymerase chain reaction with reagents from Applied Biosystems. Results . In a group of patients with AK and the controls the most frequent haplotypes were AGG and TGA. Haplotype TG (-917A>T and -988-4G>T) containing the promoter T allele of 917A>T was more frequent in patients who had AK onset before the age of 70 years (0.6117 vs. 0.417; p = 0.029) and with more extensive skin lesions (0.6085 vs. 0.414; p = 0.029). Haplotype TA (-988-4G>T and -1107G>A), containing the protective G allele of -988-4G>T, was observed only in patients with AK. There was no presence of haplotype TA in patients with coexisting SCC (the result was near statistical significance, p = 0.059). Conclusions . The results of the study suggest the necessity of analysis of haplotypes in evaluation of predisposition to precancerous skin lesions and skin cancers.